Routes of Vitamin B12 Supplementation: Clinical Evidence, Limitations, and Practical Considerations - Semianiuk, Alina; Stopa, Małgorzata; Szczęsna, Ewa; Drymluch, Paweł; Lewicka, Wiktoria; Szaliński, Konrad; Sośniak, Izabella; Moreń, Adrianna (Quality in Sport, 2025)
Introduction and purpose Vitamin B12 deficiency remains an underdiagnosed condition with significant hematological, neurological, and psychiatric consequences. The aim of this review is to evaluate and compare the efficacy, indications, and clinical applicability of oral, sublingual, intramuscular, and subcutaneous vitamin B12 supplementation routes, and to provide evidence-based recommendations tailored to patient-specific conditions. Brief description of the state of knowledge Vitamin B12 is primarily absorbed in the distal ileum via an intrinsic factor-mediated mechanism. Deficiency is commonly caused by malabsorption syndromes, restrictive diets, medication use, and autoimmune disorders such as pernicious anemia. Intramuscular and subcutaneous administration bypass absorption defects and are considered the gold standard, especially in symptomatic patients. Oral and sublingual routes are increasingly used due to ease of use and cost-effectiveness. Sublingual supplementation, in particular, shows comparable biochemical efficacy to intramuscular injection and offers higher patient satisfaction. However, the variability in absorption and the use of surrogate biomarkers limit the consistency of clinical outcomes across studies. Summary All forms of vitamin B12 supplementation can be effective when used appropriately. Intramuscular administration remains superior in cases of severe deficiency and neurological involvement. Oral and sublingual supplementation are suitable for long-term maintenance and mild deficiencies, especially in patients with adherence capacity and no profound malabsorptive conditions. Clinical decision-making should be guided by etiology, severity, patient preference, and logistical feasibility.